Kebutuhan Mahasiswa Berbahasa sebagai Bahan Redesain Silabus Mata Kuliah Bahasa Indonesia - Hastari Mayrita; Ayu Puspita Indah Sari; Mardhotillah Mardhotillah (SAP (Susunan Artikel Pendidikan), 2022)
There is a need for standards to set linguistic or language standards, or determine language parameter policies required by students. Analysis of language needs is one of the strategies to determine the proposed language policy in the field of education. One of them is by examining student needs for language learning as a material for redesigning the Indonesian Language Course Syllabus. The research focus is oriented to the needs of students reviewed based on an analysis of students' language needs in Indonesian Language Courses, as a material for redesigning the Indonesian Language Course syllabus in Bina Darma University, 2022. The researcher uses a qualitative method with a case study approach. The data collection techniques was a questionnaire. Data analysis used content analysis. For the credibility of the research, the researcher did member checking. The results of the study discovered students' difficulties in language and students' needs for language skills as material for redesigning the syllabus for Indonesian Language Courses in Universities.